Synthesis of the Taxol core using asymmetric 1,4-additions - Wang, JY (2020)
The topic of this thesis is the synthesis of Taxane derivatives using the asymmetric conjugate addition of alkenes. Taxol is an important anti-cancer drug and owing to its complex structure, remains a subject of fascination by chemists. The asymmetric conjugate addition of alkenes is a power transformation and holds promise in synthesising complex molecules such as Taxol. In Chapter 1, we prove that this is a feasible undertaking by synthesising the C-ring of the Taxol core containing the C8 stereocenter. A complex nucleophile containing a bromide and substituted alkene was successfully synthesised on decagram scale and underwent asymmetric conjugate addition to give this intermediate in 95% yield and 88% ee.